Clinical Efficacy of a Novel Therapeutic Principle, Anakoinosis - Heudobler, Daniel; Rechenmacher, Michael; Lüke, Florian; Vogelhuber, Martin; Klobuch, Sebastian; Thomas, Simone; Pukrop, Tobias; Hackl, Christina; Herr, Wolfgang; Ghibelli, Lina; Gerner, Christopher; Reichle, Albrecht (Frontiers in Pharmacology, 2018)
Is it possible to communicatively reprogram, reboot, metastatic therapy-resistant tumors for achieving long-term tumor control? Communicative reprogramming of tumor tissues, i.e. anakoinosis, aims at establishing novel communicative behavior of tumor tissue, the hosting organ and organism via re-modulating gene expression, thus recovering differentiation, and apoptosis competence leading to cancer control – in contrast to an immediate, ‘poisoning’ with maximal tolerable doses of targeted or cytotoxic therapies. The ancient Greek term "anakoinosis", means "communication". ‘Master modulators’ comprise a broad diversity of drugs, characterized by the capacity for reprogramming tumor tissues, i.e. transcriptional modulators, metronomic low-dose chemotherapy, epigenetically modifying agents, protein binding pro-anakoinotic drugs, such as COX-2 inhibitors, IMiDs etc., or for example differentiation inducing therapies. Data on 97 anakoinosis inducing schedules indicate a favorable toxicity profile: The combined administration of master modulators, frequently with poor or no monoactivity may even induce continuous complete remission in refractory metastatic neoplasia, irrespectively of the tumor type. That means recessive components of the tumor, successively developing during tumor ontogenesis, are accessible by regulatory active drug combinations in a therapeutically meaningful way. Drug selection is now dependent on situative systems characteristics, to less extent histology dependent. Novel therapy qualities, for example ‚active‘ chronification of tumor disease, or re-establishing apoptosis and differentiation competence highlight the diversified therapeutic activity profile of master modulators, inclusively nuclear receptor agonists, such as peroxisome proliferator-activated receptor (PPAR) γ/α agonists. Indeed, anakoinosis inducing therapies may circumvent the problem of ‘undruggable targets’ and may face the problem of genetic tumor heterogeneity in metastatic disease. Prognostic parameters, such as therapy refractoriness, distinct mutations in bcr-abl gene in chronic myelocytic leukemia, FLT3 positivity in acute promyelocytic leukemia may ultimately lose their exclusive unfavorable prognostic significance by induction of anakoinosis. Particularly, a late-stage prognostic parameter for pioglitazone and COX-2 inhibitor plus metronomic low-dose chemotherapy is the intensity of PPARγ expression in melanoma cells. Anakoinosis inducing therapy schedules facilitate to integrate palliative care into the trajectory of cancer care in resistant metastatic neoplasia of quite heterogeneous histologic origin. The evidences are so strong as to indicate that anakoinosis represents a substantive therapy principle besides novel targeted therapies.